(3aUd GdebGd ajeG Hjf GdTQjYI hGdMceI ef GdEJUGds - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3hHYO MeO Gddg HLejY eMGeOg aEf GdZQV ef gPG Gdhbd Cf faMU Ydi Lgi GdfXQ GdTQYi gd GdfXQ ai GdadSaI hYdhe GdefWb eHGM HGdTQY , Ce eMXhQ Ce eCehQ Hg s
(3BNQgG (B:s
(3hbO QaY Gddg cKjQkG ef gPg GdTQhQ hGdLgGdGJ hfHg GdNhGU Ydi hLhH GdfXQ GdJGe ai CUd GdTQjYI ced hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3jdjgG GdeSCdI GdJi PcQgG CHh GdhdjO ai aUd GdebGds
(3hgj ef cJH CejQ GdeDefjf RjOGf GdMSfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B228s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1261s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs